A greve política como direito: constitucionalidade, perspectivas de regulamentação e idealizações na democracia brasileira - Azevedo, Mateus Freitas (2021)
In the present dissertation, the ideal treatment given to political strike in Brazilian democracy is studied. A bibliographical and documental research is done, initially about fundamental rights, specially those linked to freedom and equality, and about important events in working class’ awareness process as collective subject of rights and political being in Brazil. Manifestations since the 1960s are narrated, until the present, with influence of innovations and technologies in the country’s politics. The implications of a democratic system and how they take effect in the Brazilian scene are also addressed, reading bibliography and international documents incorporated into the national legal system. Contemplating the history of strike institute over the years, the many facets that it can have and its conception as a fundamental right by the Constitution of 1988, in addition to the sayings that Law nº 7.783/89 brings, the strike is evaluated as a broad group, the political strike being a valid and legitimate specie of it. With the approach that political strike episodes receive and the profile that Executive, Legislative and Judiciary Powers present, the best entity to acknowledge and regulate the practice as a right is considered, defining the legislator as the appropriate figure for the task. Finally, adequate parameters are drawn for regulation of political strike in Brazil.